Entitlement to Compensation for Prolongation and Disruption Costs in Construction Projects Under Standard Forms of Contract and UAE Civil Law - KEILANI, MOHAMMAD BASEM NAIM ZAID (2025)
The dissertation examines the efficacy of the FIDIC 2017 Red Book and the UAE Civil Code (Federal Law No. 5 of 1985) in regulating the entitlement to claims for prolongation and disruption costs in construction projects. It analyses the key contractual and statutory principles governing entitlement, and explores the procedural steps, evidentiary requirements, and practical challenges contractors face in substantiating such claims. The study identifies substantial gaps and challenges within both frameworks, including the absence of defined methodologies for assessing extensions of time, concurrent delay, and disruption quantification. Adopting a doctrinal legal analysis supported by case law, the research introduces the Society of Construction Law Delay and Disruption Protocol (2nd Edition, 2017) as a non-binding guidance document that can supplement contractual and legal procedures. When contractually incorporated, the Protocol can enhance consistency, fairness, and analytical transparency, and gain greater persuasive weight before the UAE courts. However, its provisions cannot override the mandatory principles of the UAE law and must operate within their limits. The dissertation concludes that aligning the FIDIC 2017, the UAE Civil Code, and the SCL Protocol through balanced drafting can significantly improve the administration and resolution of delay and disruption claims in the UAE construction projects. Keywords: Prolongation, Disruption, FIDIC 2017, UAE Civil Code, SCL Protocol, Concurrent Delay.